2020
DOI: 10.1007/s10815-020-01942-z
|View full text |Cite
|
Sign up to set email alerts
|

Navigating assisted reproduction treatment in the time of COVID-19: concerns and considerations

Abstract: The COVID-19 pandemic has fueled numerous debates in the field of assisted reproductive technology (ART) as the effect of SARS-CoV-2 on pregnancy and infancy is still considered uncharted territory. Various theses and recommendations on what optimal practice is have emerged, as evidenced by surveys, webinars, and recent publications. ART specialists are faced with dilemmas in light of the lack of concrete scientific evidence required to pave the way towards future safe practice. Meanwhile, infertile couples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Considering the high rate of human-tohuman transmission and viral shedding from both symptomatic and asymptomatic individuals [39], high asymptomatic to symptomatic patient ratio [40] and ability of the viruses to survive on inanimate objects for extended periods and at sub-zero temperatures [41,42], the clinics offering assisted reproduction services are at risk of spreading COVID-19 [43]. With the resumption of services for assisted reproduction in many parts of the world [44,45], the clinics must be aware of the risks that the virus poses on gametes and early embryos. Indeed, we and others have demonstrated that ACE2 is expressed in the different types of embryonic and trophectodermal cells [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high rate of human-tohuman transmission and viral shedding from both symptomatic and asymptomatic individuals [39], high asymptomatic to symptomatic patient ratio [40] and ability of the viruses to survive on inanimate objects for extended periods and at sub-zero temperatures [41,42], the clinics offering assisted reproduction services are at risk of spreading COVID-19 [43]. With the resumption of services for assisted reproduction in many parts of the world [44,45], the clinics must be aware of the risks that the virus poses on gametes and early embryos. Indeed, we and others have demonstrated that ACE2 is expressed in the different types of embryonic and trophectodermal cells [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Although most children conceived using ART are healthy, individual differences still exist, which has resulted in concern about ART and the health of mothers and babies (7). Therefore, exploration of the factors affecting perinatal and infant health after ART has important clinical value in paving the way for targeted intervention measures and reducing the impact of ART on mothers and infants (8).…”
Section: Discussionmentioning
confidence: 99%
“…It is of paramount significance to ensure that publications of research on COVID-19 are more regulated. Until this informational overload that bombards the scientific community is effectively managed, clinicians should abide by an ethical, moral, and legal duty towards their patients regarding shared decision making, while prioritizing patients’ safety [ 105 ].…”
Section: Discussionmentioning
confidence: 99%